Rapid Organocatalytic Formation of Carbon Monoxide: Application towards Carbonylative Cross Couplings. Issue 43 (9th July 2020) - Zoller, Ben; Zapp, Josef; Huy, Peter H.
Abstract: Herein, the first organocatalytic method for the transformation of non‐derivatized formic acid into carbon monoxide (CO) is introduced. Formylpyrrolidine (FPyr) and trichlorotriazine (TCT), which is a cost‐efficient commodity chemical, enable this decarbonylation. Utilization of dimethylformamide (DMF) as solvent and catalyst even allows for a rapid CO generation at room temperature. Application towards four different carbonylative cross coupling protocols demonstrates the high synthetic utility and versatility of the new approach. Remarkably, this also comprehends a carbonylative Sonogashira reaction at room temperature employing intrinsically difficult electron‐deficient aryl iodides. Commercial 13 C‐enriched formic acid facilitates the production of radiolabeled compounds as exemplified by the pharmaceutical Moclobemide. Finally, comparative experiments verified that the present method is highly superior to other protocols for the activation of carboxylic acids. Abstract : Double formicable : A simple formamide catalyst enables the rapid transformation of formic acid into carbon monoxide (CO) using inexpensive trichlorotriazine (TCT). Application towards four different carbonylative cross couplings down to room temperature showcases high levels of synthetic utility and versatility. The organocatalytic ex situ formation of CO using commercial H 13 CO2 H allows the synthesis of radiolabeled compounds such as the drug Moclobemide.